A retrospective analysis of factors associated with the length of hospital stay in COVID-19 patients treated with Nirmatrelvir / Ritonavir - Zheng, Jiantao; Hong, Wencong; Zhou, Chanjuan; Hong, Donghuang; Yan, Hong; Shen, Yanghui (Frontiers in Pharmacology, 2023)
Objectives: This study reviewed factors influencing the length of hospital stay in adult inpatients with confirmed Coronavirus disease (COVID-19) who were treated with Nirmatrelvir/Ritonavir. Methods: We did a retrospective analysis of data from a cohort of inpatients with confirmed diagnosis of Omicron variant of SARS-CoV-2 infection who were treated with Nirmatrelvir/Ritonavir. We included patients who were treated from 13th March 2022 to 6th May 2022 in various in-patient treatment units in Quanzhou, Fujian Province, China. The primary study outcome was the length of hospital stay. Secondary study outcome was viral elimination defined as negative for ORF1ab and N genes [cycle threshold (Ct) value ≥35 in real-time PCR], according to local guidelines. Hazard ratios (HR) of event outcomes were analyzed using Multivariate Cox regression models. Results: We studied 31 inpatients with high risk for severe COVID-19 who were treated with Nirmatrelvir/Ritonavir. We found that inpatients with shorter length of hospital stay (≤17 days) were mostly females with lower body mass index (BMI) and Charlson Comorbidity Index (CCI) index. Their treatment regimen with Nirmatrelvir/Ritonavir was started within 5 days of diagnosis (p < 0.05). Multivariate Cox regression indicated that inpatients starting treatment of Nirmatrelvir/Ritonavir within 5 days had a shorter length of hospital stay (HR 3.573, p = 0.004) and had a faster clearance of viral load (HR 2.755, p = 0.043). Conclusion: This study assumes relevance during the Omicron BA.2 epidemic as our findings suggest that early treatment with Nirmatrelvir/Ritonavir within 5 days of diagnosis (≤5 days) was highly effective in shortening the length of hospital stay and faster viral load clearance.